Lateral Transorbital Approach for Lateral Sphenoid Defects: Anatomy, Surgery, Nasoseptal Flap Use, and a 4‐Case Series - Darlene Lubbe; Lien Deschuytere; Kris S Moe (Laryngoscope Investigative Otolaryngology)
ABSTRACT Objectives To assess the effectiveness and anatomical advantages of the lateral transorbital approach for complex skull base repairs in the lateral recess of a pneumatized sphenoid sinus and compare it to standard transnasal methods. Methods Case series of four patients across two institutions (Otorhinolaryngology and Neurosurgery departments in Cape Town, South Africa, and Seattle, USA). Three patients with spontaneous cerebrospinal fluid (CSF) leaks underwent a pure lateral transorbital repair; one patient with skull base fractures from a gunshot wound received a combined transnasal and transorbital repair with a nasoseptal flap through the lateral transorbital corridor. Results The lateral transorbital approach effectively accessed the lateral sphenoid recess in all patients, allowing repair with standard zero‐degree tools while avoiding nasal morbidity and hypesthesia associated with the transpterygoid access. When necessary, an ipsilateral nasoseptal flap can be utilized for complex defects, with placement under direct vision through the lateral transorbital route. The flap provides sufficient length to extend into the lateral corridor up to the temporalis muscle when required. Conclusions The lateral transorbital approach enhances visualization, reduces nerve injury risk, and lowers nasal morbidity, making it a valuable method for repairing pneumatized sphenoid sinus defects. The nasoseptal flap provides versatile and effective CSF leak prevention in transorbital procedures. Level of Evidence 4.